STRUCTURAL-GEOMETRICAL PARAMETERS OF THE HEART IN MEN WITH CHRONIC HEART FAILURE DEPENDING ON THE BODY MASS INDEX - Bidzilya, P. (World of Medicine and Biology, 2016)
The changes in structural and geometric parameters of the heart in men with chronic heart failure depending on the body mass index were investigated. It is established that in the presence of obesity in men with CHF there is a more significant dilatation of the aorta, right heart and there is a trend towards the predominance of the size of the left ventricle, parallel to a more pronounced hypertrophy of the myocardium. Patients with normal weight tend to be a great manifestation from the calcination of valves, distribution pulmonary and deepening of the mitral, aortic and tricuspid regurgitation. Among the respondents with overweight was observed the distribution of the mitral, aortic, tricuspid and deepening pulmonary regurgitation.
Keywords: chronic heart failure; men; structural-geometric heart changes; body mass index